2018
DOI: 10.1097/scs.0000000000004265
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Postmeningitic Deafness

Abstract: Cochlear implantation after postmeningitic deafness has favorable outcomes especially in long term. Although this type of inner ear pathology may require special considerations during surgery, it is a relatively safe procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
1
4
0
3
Order By: Relevance
“…Polymorphonuclear invasion, fibrosis and/or angiogenesis, osteoid deposition, and mineralization were described as early as 2 weeks to 2 months from the beginning of this process . Different studies have demonstrated the location of new bone formation in TB with labyrinthitis ossificans . Our findings are consistent with other studies that showed the presence of new bone formation beginning at the lower segments of the cochlea .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Polymorphonuclear invasion, fibrosis and/or angiogenesis, osteoid deposition, and mineralization were described as early as 2 weeks to 2 months from the beginning of this process . Different studies have demonstrated the location of new bone formation in TB with labyrinthitis ossificans . Our findings are consistent with other studies that showed the presence of new bone formation beginning at the lower segments of the cochlea .…”
Section: Discussionsupporting
confidence: 91%
“…Previous otopathological studies have suggested that SNHL following meningitis occurs due to the spread of the infection from the meninges to the labyrinth via three routes, including (a) the cochlear aqueduct and the cochlear modiolus (meningogenic), (b) the vascular support of the inner ear (hematogenic), or (c) the oval and round windows (tympanic routes) . Once in the labyrinth, inflammatory mediators may induce severe labyrinthitis and disrupt the blood‐labyrinth barrier, resulting in hearing and vestibular loss …”
Section: Introductionmentioning
confidence: 99%
“…Foram propostos os mecanismos de danos ao sistema auditivo central e periférico secundários à meningite, nos quais o último é o mais comumente afetado (Nichani et al, 2011;Tokat et al, 2018). Estudos otopatológicos prévios sugerem que a perda auditiva neurossensorial após a meningite ocorre devido à disseminação da infecção para o labirinto pelas seguintes rotas (Nabili et al, 1999;Xu;Joglekar;Paparella, 2009;Nichani et al, 2011;Kaya;Cureoglu, 2016): a) aqueduto coclear e modíolo da cóclea (disseminação meningogênica); b) suporte vascular da orelha interna (disseminação hematogênica).…”
Section: Perda Auditiva Após Meningiteunclassified
“…Uma vez no sistema labiríntico, os produtos bacterianos e mediadores inflamatórios podem induzir labirintite grave e perturbar a barreira labirinto-sangue, resultando em perda auditiva (Juhn;Hunter;Odland, 2001;Nichani et al, 2011;Kaya;Cureoglu, 2016;Tokat et al, 2018).…”
Section: Perda Auditiva Após Meningiteunclassified
See 1 more Smart Citation